Los juegos tradicionales para mejorar la motivación en los niños y niñas de 5 a 6 años de la unidad educativa Adolfo Valarezo del cantón Loja, período 2018-2019. - Robles Puchaicela, Jessica Magaly (2019)
Traditional games begin to be erased from the memory of today's children. Since they are traces of the past and are part of the culture of the peoples, children learn to transmit their cultural identity, to keep them alive in time; This research entitled: Traditional games to improve the motivation of children from 5 to 6 years of educational unit "ADOLFO VALAREZO" of the CANTON LOJA, period 2018-2019, whose general objective is: to determine the influence of traditional games on the motivation of children between 5 and 6 years of age of the educational unit "Adolfo Valarezo", the methods used were: Scientific method, inductive method, descriptive method and Explanatory method; and as techniques and instruments the observation sheet that was applied to 20 children, the survey to 4 educators of first basic education. The most relevant results determined that 10% of the children investigated had a low level of development in terms of their motivation with the use of traditional games; reaching a satisfactory level of 100% after applying our alternative proposal. It is concluded that traditional games to improve motivation are of paramount importance for children to develop their skills and skills in each of their ages, without any rejection by their peers because they can not make one or another Activity, as well as transmitting our cultural identity. It is therefore recommended to apply our alternative future proposal to children 5 to 6 years old from the educational establishments of our city.